Muslim psychologists in facing challenges of the 4.0 industrial revolution - Syaidatun Nazirah Abu Zahrin,; Rezki Perdani Sawai,; Joki Perdani Sawai,; Che Sulaila Che Harun, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The 4.0 industrial revolution (4IR) is one of the biggest challenges faced by every individual, especially psychologists of this century. In this article, the authors will examine the preparation for challenges psychologists face in helping individuals deal with the psycho-social impact of the 4.0 industrial revolution. 4IR comprises of ten pillars: automation robots, simulations, system integration, multi-purpose internet, cyber security, public computing, additional material creation, reinforced reality, large data analysis, and system integration. This conceptual paper covers articles and books from year 1998 to 2020. This article aims to help psychologists become more knowledgeable about how their disciplinary expertise can assist in discussions, research, and policy initiatives relating to 4.0 Industrial Revolution. Therefore, the objective of this paper is to outline the challenges faced by the Muslim psychologists in the era of 4.0 Industrial Revolution and how to deal with the challenges diligently. Psychologists are responsible for designing and implementing interventions to deal with the psycho-social impact of the 4.0 Industrial Revolution. Psychologists’ involvement is needed to increase psychological support to individuals, in particular, and to society as a whole. Hence, the mental health and mental strength of psychologists are important in preparation for the 4IR challenge.